MVC Frameworks in Web Development - Kolu, Aku (2012)
With the increased demand of complex, well-scalable and maintainable web applications, the MVC architecture is increasing in popularity and frameworks (whether they utilize the MVC architecture or not) are quickly becoming de facto –standard in web development. This Bachelor’s Thesis introduces the use of MVC architecture in web development and how several web application frameworks make use of it. This research introduces the concepts of both the MVC architecture and web application frameworks but does not go into the basics of web development. Three examples of web application frameworks that utilize the MVC architecture are introduced. Due to the constraints provided by the size of this research, this paper does not have a thorough comparison between the three frameworks. Instead, it focuses on finding out how each framework provides answer to certain complexity often required in today’s modern Web 2.0 applications.